Characterizing dynamical processes in surface-bound exospheres via resolved sodium D emissions - Lierle, Patrick; Lovett, Emma; Schmidt, Carl; Merkel, Aimee (Frontiers in Astronomy and Space Sciences, 2025)
Two techniques to quantify the energy of an atmospheric gas remotely are the emission scale height and linewidth spectroscopy at high spectral resolution. In the latter, temperature, or effective temperature in the case of a collisionless exosphere, may be retrieved analytically for a single-component transition line, or by forward-modeling for transition lines with fine structure. Temperatures derived from linewidths and from scale heights need not necessarily agree, as each probes different characteristics. In fact, discrepancy between these quantities can actually reveal additional processes and the breakdown of implicit assumptions. Here, sodium D line profiles as a function of altitude are compared for the terrestrial exospheres of Mercury, the Moon, and Europa. At Mercury, effective temperature near the surface is 1,200–1500 K, consistent with MESSENGER scale heights. Away from the sub-solar point, gas linewidths are Doppler broadened, most notably down the comet-like escaping tail where effective temperatures reach >7500 K and line profiles become distinctly non-thermal in shape. We interpret this broadening as due to gravity removing the lowest energy atoms from the observed line-of-sight velocity distribution function. Growth in Doppler broadening ceases at the apex distance of ballistic bound atomic trajectories, effectively defining a boundary beyond which all gas escapes. Transitions from bound to escaping gas are expected to be universal in line profiles of planetary exospheres, and Mercury’s emissions are exemplar. Doppler broadening with altitude at the Moon and Europa cannot be attributed to this effect, however, and both offer important comparisons. Lunar sodium line profiles exhibit broadening on scales far too small for significant differences in the partitioning of bound and escaping gas, and instead superposed populations supplied by different source mechanisms may offer an explanation. Sodium linewidths at Europa continue to increase well beyond this satellite’s Hill sphere, an influence of their Keplerian motion around Jupiter. In each of these three cases, emission line morphology offers a novel diagnostic for evaluating the processes that promote atmospheric escape.